One Health at gunpoint: Impact of wild boars as exotic species in Brazil - A review - Louise Bach Kmetiuk; Leandro Menegueli Biondo; Felipe Pedrosa; Giovani Marino Favero; Alexander Welker Biondo (One Health, 2023)
Wild boars have been listed among the 100 most invasive species worldwide, spreading impacts to all continents, with the exception of Antarctica. In Brazil, a major source of introduction was a commercial livestock importation for exotic meat market, followed by successive escapes and releases to natural ecosystems. Currently found in all six Brazilian biomes, with reports in 11 Brazilian states, wild boars have invaded natural and agricultural areas. Wild boars have been reportedly indicated as hosts and reservoirs of several zoonotic diseases in Brazil, including toxoplasmosis, salmonelosis, leptospirosis, brucellosis, tuberculosis, trichinellosis, and hepatitis E. Wild boars have been also associated with Brazilian spotted fever and rabies, infected while providing plentiful exotic blood supply for native ticks and hematophagous bats. Due to their phylogenetic proximity, wild boars may present ecological niche overlapping and direct disease risk to native white-lipped and collared peccaries. Moreover, wild boars may post an economical threat to Brazilian livestock industry due to restrictive diseases such as Aujeszky, enzootic pneumonia, neosporosis, hemoplasmosis, and classic swine fever. Finally, wild boars have directly impacted in environmentally protected areas, silting up water springs, rooting and wallowing native plants, decreasing native vegetal coverage, disbalancing of soil components, altering soil structure and composition. Wild boar hunting has failed as a control measure to date, according to the Brazilian Ministry of Environment, due to private hunting groups mostly targeting males, intentionally leaving females and piglets alive, disseminating wild boar populations nationwide. Meanwhile, non-government animal welfare organizations have pointed to animal cruelty of hunting dogs and wild boars (and native species) during hunting. Despite unanimous necessity of wild boar control, eradication and prevention, methods have been controversial and should focus on effective governmental measures instead occasional game hunting, which has negatively impacted native wildlife species while wild boars have continuously spread throughout Brazil.